SAT0659 Is synovial hypertrophy without doppler activity in rheumatoid arthritis joints sensitive to change? – results of a longitudinal ultrasound study. (12th June 2018) - Terslev, L.; Østergaard, M.; Sexton, J.; Hammer, H.B.
Abstract : Background: Ultrasound (US) is used to assess diseases activity in rheumatoid arthritis (RA). Grey scale (GS) US shows the synovial hypertrophy (SH) and Doppler the amount of hyperemia which is believed to reflect disease activity. Some joints with SH may have no Doppler activity despite the use of high-end US equipment and these joints are generally believed to be inactive without potential to change. Objectives: The aim was to investigate if joints with SH but no Doppler activity is sensitive to change during treatment with biological DMARD (bDMARD) in RA patients. Methods: RA patients initiating or changing bDMARD treatment were included. US examination was performed at baseline, 3 and 6 months using Siemens Antares US equipment with Doppler settings for slow flow. 36 joints were evaluated at each visit. SH and Doppler activity was graded from 0–3 according to the US atlas by Hammer et al.( 1 The GS score for SH in joints without Doppler activity was registered for the individual joints using GS SH ≥1 as threshold. The changes were compared to changes in SH in joints with Doppler activity. Results: 151 patients (82.8% women, 80.1% seropositive for anti-CCP) were included, with a mean (SD) age 51.4 (13.2) years, disease duration 9.9 (7.9) years. At baseline, 50.7% used prednisolone (mean (SD) 5 mg (4.68)). The patients had a mean (SD) baseline DAS28 of 4.5 (1.5). At baseline 23% of the joints had SH without Doppler activity and 23% of the joints had SH with Doppler activity. Doppler-negative joints had overall lower grades of SH (mean 1.2) than Doppler-positive joints (mean 2.2) at baseline using GS SH >1 as cut-off. The improvement in SH was similar in Doppler-positive and Doppler-negative joints but when adjusting for the baseline score of SH, Doppler-negative joints had a higher tendency towards decrease than Doppler-positive joints for all grades (3 months: p<0.0001; 6 months=0.0006). A weak correlation was found to changes in DAS 28(crp) (Doppler-negative joints:0.27 (p=0.001) and 0.18 (p=0.03) at 3 and 6 months respectively – Doppler-positive joints: 0.25 (p=0.004) and 0.33 (p=0.0002) at 3 and 6 months respectively). Conclusions: SH in joints without Doppler activity improves during bDMARD, i.e is sensitive to change. Thus, SH without Doppler activity is not a sign of inactive disease. These findings document that both Doppler and SH should be evaluated when assessing disease activity by US. Reference: [1] Hammer HB, Bolton-King P, Bakkeheim V, et al. Examination of intra and interrater reliability with a new ultrasonographic reference atlas for scoring of synovitis in patients with rheumatoid arthritis. Ann Rheum Dis2011;70:1995–8. Disclosure of Interest: None declared